Baboon route repetition in a seasonal environment - Lewis-Bevan, Lynn; Hammond, Philippa; Carvalho, Susana; Biro, Dora (Frontiers in Ecology and Evolution, 2025)
IntroductionRoute-based navigation is a common movement strategy for a variety of taxa, wherein animals repeatedly re-use familiar paths during travel. However, this type of navigation is understudied in wild animals that experience regular displacement, raising questions about the robustness and longevity of such routes and route memories. The seasonal flooding of Gorongosa National Park, Mozambique, provides an opportunity to test multiple facets of route-based navigation in wild primates, due to its high seasonality and annual flooding.MethodsData was collected from GPS collars placed on four chacma baboons in two troops in Gorongosa National Park. Using GPS points taken every 15 minutes, we use nearest-neighbour analysis to compare daily paths across the year, to identify high-use paths. We then look at the identified high-use paths to see if they are used across the entire study period, with a focus on areas that were vacated for more than two months of the study period.ResultsWe find that the baboons do have vacated areas, but return to the same areas after displacement. We did not find high-use routes in these areas used both before and after displacement, although high-use routes did exist that were used across the study period in different areas.DiscussionOur results indicate that routes may not be maintained in long-term memory spanning several months, or that route reuse is in part dependant on seasonal resources or navigational aids. Although the study period did not span a full year, this study presents a replicable method of analysing route reuse and identifying high-use routes without traditional methods of manually overlaying and analysing daily paths.